PENERAPAN MODEL TAKE AND GIVE UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS DAN SELF CONFIDENCE PESERTA DIDIK SMP - Muhammad Hilmy Ramdhani; Usep Kosasih (Universitas Islam Nusantara, 2021)
This research is based on the low level mathematical understanding ability of students. One alternative learning model that can be applied to improve the mathematical understanding ability is the Take and Give model. The research objective is to find out: the improvement of students' mathematical understanding ability, Self Confidence of students towards the application of the Take and Give and Problem- based learning model. The method used is quasi-experimental method, with noneequivalent research design control group pretest - posttest design. The research was conducted in one of the State Junir High Schools in Bandung. The instrument used is a mathematical understanding ability test, and a Self Confidence student questionnaire. Based on the analysis of the results of the mathematical understanding ability test, it can be concluded that the increase in students' mathematical understanding ability using the Take and Give model as good as the students who use the Problem- based learning model. Take and Give model can have a positive effect on students Self Confidence.